Subverting Subversion: A Review on the Breast Cancer Microenvironment and Therapeutic Opportunities - Rothschild, Ethan; Banerjee, Debabrata (Breast Cancer: Basic and Clinical Research, 2015)
This review combines the recent research on the subject of tumor immunology and methods of correcting the immune system's reaction to the tumor microenvironment while impeding the survival and growth of tumor cells, with a focus on breast cancer. Induction of hypoxia-inducible genes in the microenvironment leads to lowering of its pH. This impedes the adaptive immune response and acts to recruit cells of the immune system, which suppress the immune response. Regulatory T-cells (Tregs), myeloid-derived suppressor cells (MDSCs), and their derivatives coordinate an anti-autoimmunity response and a healing response in concert with tumor-secreted cytokines, enzymes, and antigens. Together, they suppress a proper immune reaction to tumor cells and promote cellular reproduction (Fig. 1). In addition, the hypoxia-inducible response and components of the tumor microenvironment such as cancer-associated fibroblasts (CAFs) also create an ideal environment for tumor growth and metastasis via neoangiogenesis and increased motility. Broad-spectrum chemotherapy drugs are problematic as breast cancer cells develop resistance through selective loss of a novel target and downregulation of apoptotic factors. A better understanding of the tumor microenvironment offers new therapeutic opportunities to rescue the immune response, inhibit cancer cell growth pathways, and subvert the tumor microenvironment with little toxicity and side effects.